THE EFFECT OF MOTIVATION,WORK ENVIRONMENT AND LEADERSHIPETYLE ON WORK ACHIEVEMENT THROUGH THE PERFOMANCE OF MEMBERS OF THE TRAFFIC DIRECTORATE RIAU ISLANDS POLDA - Riki Iswoyo; Indrayani; Muammar Khaddafi; Diana Titik (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Based on the Preamble of the 1945 Constitution, it has been clearly stated that the purpose of the Republic of Indonesia is to protect the entire Indonesian nation and all of Indonesia's bloodshed, promote public welfare, educate the nation's life, implement world order based on freedom, eternal peace and social justice. The police have an important role in the state order, where the role of the police is to assist the state in enforcing the regulations contained in the law. One of the rules enforced by the police is the rules in traffic, considering that the mobilization of people with vehicles is increasing rapidly, the greater the conflicts that occur in the world of traffic. This also applies to the Riau Islands Regional Police which is under the auspices of the Riau Islands Police Traffic Directorate.